Building a resilient twenty-first-century economy for rural America - Albrecht, Don E., author; Utah State University Press, publisher (Colorado State University. Libraries, 2020)
Rural communities have traditionally been dependent on goods-producing industries. What happened as employment in these industries has declined? Provides a path a twenty-first-century economy can be built. Describes how economic changes led rural voters to support Trump and why his policies won't relieve rural economic problems.--Provided by publisher.
Manufacturing -- Agriculture -- The coal industry -- Fracking, horizontal drilling and oil and gas production -- Northwest forests and the logging industry -- Mineral development -- Amenity and tourism communities -- Federal environmental policies and rural economic development -- Federal land management and rural economic development -- Building a 21st century economy for rural America.
Keywords: Rural development -- United States